2011
DOI: 10.1089/jpm.2011.0131
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Palliative Care Services on the Aggressiveness of End-of-Life Care in the Veteran's Affairs Cancer Population

Abstract: Cancer care near the EOL has become more aggressive with time at one of the hospitals in the Veterans Affairs healthcare system (VAHS). Institution of a PCS service was unable to completely decrease this trend of increasing aggressiveness of cancer care near the EOL. However, timely PCS consults may help attenuate this aggressiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
74
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(80 citation statements)
references
References 14 publications
5
74
1
Order By: Relevance
“…A previous retrospective study [30] showed that patients with advanced gynecologic malignancies followed up by PC teams, especially when follow-up occurred for more than two weeks before death, received less chemotherapy, sought emergency care less often and had lower rates of hospital and Intensive Care Unit stay for more than 14 days compared with patients not receiving PC. In a multivariate analysis involving age, staging, tumor type and race, receiving PC in a timely manner was the only significant predictor of fewer invasive measures at the end of life.…”
Section: Discussionmentioning
confidence: 99%
“…A previous retrospective study [30] showed that patients with advanced gynecologic malignancies followed up by PC teams, especially when follow-up occurred for more than two weeks before death, received less chemotherapy, sought emergency care less often and had lower rates of hospital and Intensive Care Unit stay for more than 14 days compared with patients not receiving PC. In a multivariate analysis involving age, staging, tumor type and race, receiving PC in a timely manner was the only significant predictor of fewer invasive measures at the end of life.…”
Section: Discussionmentioning
confidence: 99%
“…The VAMC has embarked on an ambitious training program to have palliative care available in all regions and settings (http://www.va.gov/GERIATRICS/guide/longtermcare/ Hospice_and_Palliative_Care.asp). Long-term data on outcomes from the VAMC expansion are not yet available, but preliminary data suggest that palliative care consultations can reduce the growing aggressiveness of care and use of critical care services, but only if given early in the disease trajectory and not during the terminal admission (40).…”
Section: Models That Workmentioning
confidence: 99%
“…8,9 However, rates have been slowly rising over the last decade, and 5% to 22% of all patients with advanced cancer receive chemotherapy within 2 weeks of death. [2][3][4][10][11][12][13][14][15][16][17][18] Previous research on chemotherapy administration at EOL has primarily focused on predictors and outcomes. Although these studies have helped to identify the scope of the problem, few have examined when and how oncologists discontinue chemotherapy, including how the timing influences patient outcomes.…”
Section: Introductionmentioning
confidence: 99%